Investigation of the local scour depth of a pile foundation on the migrating sand waves seabed in the western South China Sea - Xie, Botao; Sun, Hang; Liu, Tao; Tan, Haiyue (Frontiers in Earth Science, 2024)
In the western South China Sea, the diversity and complex genesis of sand waves lead to difficulties in measuring the actual scour depth of offshore wind turbine foundations. The present study employs methods such as in-situ multibeam echo sounding along with numerical simulation techniques, combined with regional hydrological and geological data, to reveal the scour depth of pile foundations under seabed sand wave migration conditions（SPF-SWM）. Unlike previous studies, this study examines pile foundation scour depth from both macroscopic and microscopic perspectives, and proposes a method for risk assessment and safety zoning during the service life of pile foundations（RASZ）. Our findings demonstrate that the dominant flow directions in the modern hydrodynamic environment play a crucial role in shaping and migrating sand waves, providing guidance for macro-level offshore wind project siting. Moreover, the study quantifies the changes in pile foundation elevations during sand wave migration and assesses their impact on safety throughout the service life of various pile foundations. Additionally, by utilizing Flow3D's numerical model and combining it with sampling data, the maximum scour depth likely to be experienced by pile foundations was calculated, establishing a micro-perspective on the range of pile foundation scour and analytically examining the coupling mechanism between sand wave migration and pile foundation scour in stages. By considering SPF-SWM, we estimated the actual depth variations of pile foundations in the study area, enabling effective assessment of scour conditions during their service life. This also provides ideas for delineating safety and risk zones, thereby offering precise locational analysis for the construction planning of offshore wind farm pile foundations.